Effects of Glucosinolate-Derived Isothiocyanates on Fungi: A Comprehensive Review on Direct Effects, Mechanisms, Structure-Activity Relationship Data and Possible Agricultural Applications - Plaszkó, Tamás (J Fungi (Basel), 2021)
Plants heavily rely on chemical defense systems against a variety of stressors. The glucosinolates in the Brassicaceae and some allies are the core molecules of one of the most researched such pathways. These natural products are enzymatically converted into isothiocyanates (ITCs) and occasionally other defensive volatile organic constituents (VOCs) upon fungal challenge or tissue disruption to protect the host against the stressor. The current review provides a comprehensive insight on the effects of the isothiocyanates on fungi, including, but not limited to mycorrhizal fungi and pathogens of Brassicaceae. In the review, our current knowledge on the following topics are summarized: direct antifungal activity and the proposed mechanisms of antifungal action, QSAR (quantitative structure-activity relationships), synergistic activity of ITCs with other agents, effects of ITCs on soil microbial composition and allelopathic activity. A detailed insight into the possible applications is also provided: the literature of biofumigation studies, inhibition of post-harvest pathogenesis and protection of various products including grains and fruits is also reviewed herein.